'Voting with dollars': a cross‐polity and multilevel analysis of political consumerism. (30th March 2015) - Zhang, Xinzhi; Wahlen, Stefan; Laamanen, Mikko
Abstract In addition to canonical political actions, political consumerism, i.e. using market purchases to express political and societal concerns, is becoming a new form of political participation, and it varies significantly among societies. Two society‐level distinctions would account for such variations: the level of political freedom and the level of economic development. Using data from the 2004 International Social Survey Program, multilevel models estimate the effects of both individual and structural factors on individuals' political consumerism, i.e. boycotting certain products, across 21 countries (n = 30 666). Political consumerism takes place in affluent countries with lower levels of political rights but higher levels of civil liberties. Individual‐level political media uses, political orientation and demographics account for boycott behaviours as well. Furthermore, canonical discriminant analysis differentiates political consumption from other types of political behaviours. The study reveals that political consumerism results from the impacts of both individual characteristics and societal determinants.